2009
DOI: 10.1042/bj20081448
|View full text |Cite
|
Sign up to set email alerts
|

The C-terminus of GLUT4 targets the transporter to the perinuclear compartment but not to the insulin-responsive vesicles

Abstract: Postprandial blood glucose clearance is mediated by GLUT4 (glucose transporter 4) which is translocated from an intracellular storage pool to the plasma membrane in response to insulin. The nature of the intracellular storage pool of GLUT4 is not well understood. Immunofluorescence staining shows that, under basal conditions, the major population of GLUT4 resides in the perinuclear compartment. At the same time, biochemical fractionation reveals that GLUT4 is localized in IRVs (insulin-responsive vesicles). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 39 publications
1
16
0
Order By: Relevance
“…the stationary storage compartment. In this regard, since multiple studies have demonstrated that both the N‐ and the C‐terminus of GLUT4 play important roles in its intracellular trafficking routes and destinations, with the C‐terminus of GLUT4 being especially important for its perinuclear TGN accumulation (16,57–59), further studies are needed to clarify the interrelationships among these GLUT4 targeting sequences and the sortilin‐mediated retrograde trafficking processes revealed by this investigation. In addition, substantial amounts of sortilin are detected in GLUT4‐containing vesicles obtained by subcellular fractionation experiments (9,12,13).…”
Section: Discussionmentioning
confidence: 97%
“…the stationary storage compartment. In this regard, since multiple studies have demonstrated that both the N‐ and the C‐terminus of GLUT4 play important roles in its intracellular trafficking routes and destinations, with the C‐terminus of GLUT4 being especially important for its perinuclear TGN accumulation (16,57–59), further studies are needed to clarify the interrelationships among these GLUT4 targeting sequences and the sortilin‐mediated retrograde trafficking processes revealed by this investigation. In addition, substantial amounts of sortilin are detected in GLUT4‐containing vesicles obtained by subcellular fractionation experiments (9,12,13).…”
Section: Discussionmentioning
confidence: 97%
“…Considering that on the way to and from the plasma membrane, Glut4 passes through several intracellular compartments, interfering with the targeting sequences within the cytoplasmic termini of the transporter may inhibit not only entry into the IRVs, but upstream trafficking steps as well. Indeed, in the ‘gain of function’ experiments, it was recently demonstrated that the C‐terminus of Glut4 targets the chimera reporter protein to the perinuclear region of the cell, that is, the IRV precursor compartment, either recycling endosomes and/or TGN, but is not sufficient for its entry into the IRVs per se (51).…”
Section: Recycling Of the Irv Proteins In The Cellmentioning
confidence: 99%
“…By the same token, the cytoplasmic tail of IRAP targets this protein primarily to the IRV donor membranes but not to the IRVs (52). Still, the cytoplasmic tail of IRAP (53) as well as the C‐terminus of Glut4 (51) can confer some degree of insulin responsiveness to the reporter molecules, which, however, is less than the insulin responsiveness of wild‐type Glut4 and IRAP (51,52,54). One explanation of this phenomenon is that once a protein enters the IRV donor compartment(s), it can be captured by budding vesicles by, for example, mass action (10).…”
Section: Recycling Of the Irv Proteins In The Cellmentioning
confidence: 99%
“…GLUT4, IRAP and sortilin are targeted to the perinuclear donor membranes by their cytoplasmic domains [14,15,19,20]. Upon arriving in this compartment, these proteins can redistribute to the IRVs by mass-action [21].…”
Section: Protein Sorting Into Irvsmentioning
confidence: 99%